Empowering women in Bangladesh: a study on the problems of working women in garments industries - Osmani, Noor Mohammad; Hossen, Belayet (European Journal of Social Sciences, 2018)
Empowering Muslim women is a worldwide trend in almost all Muslim countries. Bangladesh is leading the way for all in this regard. It is constantly led by Two prominent women for almost 30 years. Women in Bangladesh remain firm and strong in almost all sectors of life. This paper describes some major problems of working women in Bangladesh, especially in garment industry which is regarded to be the second highest foreign currency earner among other sources of Bangladesh economy. In Bangladesh, there are more than six thousand garment industries where around six million people work and majority of them are women. The problems faced by these working women are extreme in nature. It may pose a serious threat to the development of Bangladesh economy. The research asserts that if these problems persist and not tackled effectively, the number of working women will gradually diminish; consequently, the economic growth of Bangladesh will stand far from its desired goal. Among the major problems faced by the working women include the following: salary discrimination due to genders, late salary payment, sexual harassment, mocking, no leave during pregnancy and sickness, inadequate medical facilities, housing problems, insufficient transportation of companies, spread of various diseases and unhygienic workplace due to industrial discharges. The research has figured out the problems through an intensive study of the previous and current research papers, books, magazines, periodicals of government and different NGOs’, surveys and newspapers. The research also reached its conclusions through personal interviews with the working women and selected administrative officers.